A crônica no jornal: uma leitura de Caio Fernando Abreu - Jovchelevich, Roberta (2005)
The research The chronicle in the newspaper: a reading of Caio Fernando Abreu has the objective to understand and to clarify the possibilities of the chronicle as journalistic and literary sort, through the study of the chronicles of the brazilian Caio Fernando Abreu (1948 - 1996), published in the newspapers O Estado de S. Paulo and Zero Hora (Porto Alegre, RS), and congregated in the book Little epiphanys (Sulina). The choice of the author if must to the predominantly literary and confessional style that it prints to its texts and that they place it in the same aesthetic tradition of Clarice Lispector, chronicler of the Jornal do Brasil in years 70. Such style contrasts excessively with the journalistic language, evidencing the origin of the chronicle: french feuilleton, sort that inaugurated the relation between media and fiction in Latin America. In Brazil, the chronicle prospered as sort of the journalism and literature, typical ambiguity of the hybridism of sorts that is fruit of the tradition of the Latin American rupture. Characterized, generally, for light texts, mood and coloquial language associates to the daily one, the chronicle have in Caio Fernando Abreu a singular author, whose introspective look standes out the condition human being. If on the other hand, it incorporates the daily one in its narratives, for another one develops inners monologues replete of sensations and feelings, very distants of the characteristic mood and the slightness of the sort. To the one in them to lean over on its chronicles, our objective was to catch variations of the sort and, at the same time, to inside investigate the function played for the chronicle inside the newspaper, in that if it relates to the formation of public-reader for the proper printed publication and, parallel, for literature. For in such a way, we appeal to the literary, communication and the journalism theories explored by authors as Antonio Candido, Walter Benjamin, Leyla Perrone-Moisés, Roman Jakobson, Muniz Sodré and Maria Helena Ferrari.